Kombinasi Pupuk NPK dengan POC Limbah Ikan terhadap pH, P-tersedia Tanah, Serapan P, dan Hasil Baby Buncis (Phaseolus vulgaris L) pada Inceptisols asal Jatinangor - Nourma Al Viandari; Anni Yuniart; Yuliati Machfud (Fakultas Pertanian Universitas Padjadjaran, 2019)
NPK compound fertilizer has the capability to improve the quality and yield of plants, but longterm application may have some effects towards soil chemical property. This study aims to find out the effect of the combination of NPK (16:16:16) and Liquid Organic Fertilizer from fish waste towards soil pH, available P, P uptake, and yield baby bean (Phaseolus vulgaris L.) on Inceptisols from Jatinangor. The experiment was conducted in October 2015 until January 2016 at Experimental Farm, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, Sumedang regency, West Java. Randomized Block Design (RBD consisted of 8 treatments and repeated three times were applied in this research. The treatments were: control (0), 1 and 0,5 dose of NPK compund fertilizer, and 0,5; 1; 1,5 doses of liquid organic fertilizer from fish waste. Significant result were detected between combinations of NPK compound fertlizer and liquid organic fertilizer from fish waste on pH, available-P, P uptake, and yield of Baby beans (Phaseolus vulgaris L.) on Inceptisols.